The Effect of Leadership, Motivation, and Work Environment on Lecturer Performance - Faudunasokhi Telaumbanua; Dadang Syaputra; Raju Gobal; Komda Saharja; Mochamad Yunus Fitriady (Advances in Human Resource Management Research, 2026)
Purpose: This study aims to analyze the effect of leadership, motivation, and work environment on lecturer performance at Politeknik Negeri Media Kreatif Medan. Lecturer performance is an important factor in improving the quality of higher education and institutional competitiveness. Research Method: This study employed a quantitative approach with an associative research design. The population consisted of 32 lecturers using a saturated sampling technique. Data were collected through questionnaires using a Likert scale. Data analysis was conducted using SPSS, including validity and reliability tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. Results and Discussion: The results showed that leadership has a significant effect on lecturer performance. Motivation and work environment have positive but insignificant relationships in the multiple linear regression model. Simultaneously, these three variables significantly affect lecturer performance. Implications: The findings indicate the importance of improving leadership quality and work motivation, and of creating a conducive work environment to enhance lecturer performance. Originality: This study provides an empirical contribution by integrating leadership, motivation, and work environment variables into a single research model within vocational education institutions.